Work-life balance in dreams: frequency and emotional tone of work-related and hobby-related dreams - Schredl, Michael; Coors, Judith; Anderson, Lilian Marie; Kahlert, Lea Katharina; Kumpf, Celine Sophie (Journal of sleep research, 2023)
As dreams reflect waking life, the so-called continuity hypothesis of dreaming, the literature showing that work-related stress affects dreams negatively is very plausible. As in waking life, hobbies are an important component in the work-life balance. In the present study, the work-life balance in dreams was studied. Overall, 1695 persons (960 women, 735 men; mean age: 53.84 ± 13.99 years) participated in an online survey entitled “Everyday life and dreams”. The data collected refer to the pre-pandemic period. The findings indicate that hobby-related dreams are more frequent in persons who often engage in their hobbies, supporting the notion of a thematic continuity. As expected, the emotional tone of hobby-related dreams was more positive compared with dreams in general and work-related dreams in particular. Interestingly, the emotional valence of hobby-related dreams was related to the valence of general emotionality towards work in waking life, supporting the idea of an emotional continuity between waking and dreaming. The work-life balance in dreams could be defined as the difference of the percentages of work-related and hobby-related dreams; it is linked to work-related stress and the hobby frequency, factors similar to those that shift the work-life balance in waking life toward the “work” end of the spectrum.
Erstmals online veröffentlicht: 17. Juni 2022
Gesehen am 23.07.2024